Salicylic acid activates a 48-kD MAP kinase in tobacco. - Zhang, S (1997)
The involvement of phosphorylation/dephosphorylation in the salicylic acid (SA) signal transduction pathway leading to pathogenesis-related gene induction has previously been demonstrated using kinase and phosphatase inhibitors. Here, we show that in tobacco suspension cells, SA induced a rapid and transient activation of a 48-kD kinase that uses myelin basic protein as a substrate. This kinase is called the p48 SIP kinase (for SA-Induced Protein kinase). Biologically active analogs of SA, which induce pathogenesis-related genes and enhanced resistance, also activated this kinase, whereas inactive analogs did not. Phosphorylation of a tyrosine residue(s) in the SIP kinase was associated with its activation. The SIP kinase was purified to homogeneity from SA-treated tobacco suspension culture cells. The purified SIP kinase is strongly phosphorylated on a tyrosine residue(s), and treatment with either protein tyrosine or serine/threonine phosphatases abolished its activity. Using primers corresponding to the sequences of internal tryptic peptides, we cloned the SIP kinase gene. Analysis of the SIP kinase sequence indicates that it belongs to the MAP kinase family and that it is distinct from the other plant MAP kinases previously implicated in stress responses, suggesting that different members of the MAP kinase family are activated by different stresses.